Treatment of Drug Resistant Enteric Fever with an Uncertain Destination! - Ahasan, HAM Nazmul; Hossain, Homayra Tahseen (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Abstract not available J Bangladesh Coll Phys Surg 2019; 37(2): 50-52